Investigations on the substrate binding sites of hemolysin B, an ABC transporter, of a type 1 secretion system - Zohreh Pourhassan N.; Eymen Hachani; Olivia Spitz; Sander H. J. Smits; Sander H. J. Smits; Lutz Schmitt (Frontiers in Microbiology, 2022)
The ABC transporter hemolysin B (HlyB) is the key protein of the HlyA secretion system, a paradigm of type 1 secretion systems (T1SS). T1SS catalyze the one-step substrate transport across both membranes of Gram-negative bacteria. The HlyA T1SS is composed of the ABC transporter (HlyB), the membrane fusion protein (HlyD), and the outer membrane protein TolC. HlyA is a member of the RTX (repeats in toxins) family harboring GG repeats that bind Ca2+ in the C-terminus upstream of the secretion signal. Beside the GG repeats, the presence of an amphipathic helix (AH) in the C-terminus of HlyA is essential for secretion. Here, we propose that a consensus length between the GG repeats and the AH affects the secretion efficiency of the heterologous RTX secreted by the HlyA T1SS. Our in silico studies along with mutagenesis and biochemical analysis demonstrate that there are two binding pockets in the nucleotide binding domain of HlyB for HlyA. The distances between the domains of HlyB implied to interact with HlyA indicated that simultaneous binding of the substrate to both cytosolic domains of HlyB, the NBD and CLD, is possible and required for efficient substrate secretion.